2018
DOI: 10.1097/aud.0000000000000497
|View full text |Cite
|
Sign up to set email alerts
|

Binaural Pitch Fusion in Bilateral Cochlear Implant Users

Abstract: Bilateral CI listeners have abnormally broad fusion, similar to hearing aid and bimodal CI listeners. This broad fusion may explain the variability of binaural benefits for speech perception in quiet and in noise in bilateral CI users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…While not the same as sound quality measurements across ears, inter-aural pitch matching experiments have shown difficulties matching the pitch of an acoustic signal in one ear [which contains temporal fine-structure (TFS) information that is important to pitch perception] to the pitch associated with stimulation of a single electrode [which does not contain TFS information and stimulates a broader cochlear region]. Work by Reiss and colleagues [ 28 30 ] has shown that inter-aural frequency mismatch can limit binaural fusion of acoustic and electric stimulation across ears or bilateral electric stimulation. Such inter-aural frequency mismatch can also limit perception of inter-aural timing differences (ITDs) that are important for sound source localization and image fusion [ 31 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…While not the same as sound quality measurements across ears, inter-aural pitch matching experiments have shown difficulties matching the pitch of an acoustic signal in one ear [which contains temporal fine-structure (TFS) information that is important to pitch perception] to the pitch associated with stimulation of a single electrode [which does not contain TFS information and stimulates a broader cochlear region]. Work by Reiss and colleagues [ 28 30 ] has shown that inter-aural frequency mismatch can limit binaural fusion of acoustic and electric stimulation across ears or bilateral electric stimulation. Such inter-aural frequency mismatch can also limit perception of inter-aural timing differences (ITDs) that are important for sound source localization and image fusion [ 31 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from binaural fusion, there is a growing body of work showing that users of hearing aids, bilateral cochlear implants and bimodal devices have a much wider pitch fusion range than normal-hearing listeners, i.e., different monaural pitches are fused into a single binaural pitch (Reiss et al, 2017, 2018; Oh and Reiss, 2017). A similar phenomenon has been shown for vowel fusion (Reiss et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The best scores were in bilateral cochlear implant fitting followed by unilateral best implant; the least scores were in the unilateral second implant. Also, there was a gradual improvement of scores from 3 to 6 months and 6 to 12 months after the second implant fitting [20].…”
Section: Discussionmentioning
confidence: 84%